Addiction onset and offset characteristics and public stigma toward people with common substance dependencies: A large national survey experiment. (1st August 2022) - Krendl, Anne C.; Perry, Brea L.
Abstract: Drug-related overdose deaths topped 100, 000 between 2020 and 2021. Opioids and stimulants are implicated as the primary drivers of this public health crisis. Stigma remains one of the primary barriers to treatment and recovery from substance use disorders. However, little is known about how stigma varies across different substance types, whether individuals are actively using or in recovery, and medical versus recreational onset. We examined these questions using data from the 2021 Shatterproof Addiction Stigma Index, the only nationally representative data available on this topic. Respondents (N = 7051) completed a vignette-based survey experiment to assess public stigma (social distance, prejudice, competence, and causal attributions) toward people with alcohol, opioid (following a prescription pain or recreational use onset), heroin, or methamphetamine dependencies. Vignette characters were described as active users or in recovery. Adjusting for covariates (e.g., race, age, gender), prejudice and desire for social distance were highest toward heroin and methamphetamine, and lowest toward alcohol dependence. The perceived onset of the dependency affected stigma. Specifically, prescription opioids with a recreational onset were more stigmatized than those with a medical onset. Moreover, individuals depicted as being in recovery were less stigmatized than those depicted as active users. Recovery status had the largest impact on prejudice and social distance toward methamphetamine, relative to other conditions. The nature and magnitude of substance dependency stigma differs across substance types and onset and offset conditions. Reducing stigma will require tailored strategies that consider the multidimensional nature of stigma toward people with addiction. Highlights: Substance dependency is a prevalent and urgent public health problem. Stigma is a treatment barrier, but it is unknown how it varies across substances. Stigma was highest toward illicit substances, and lowest toward alcohol. Perceived onset and offset of the dependency also affected stigma. Reducing substance dependency stigma will require tailored strategies.